An Ambiguity Analysis Found In Hooray Textbook - Widyowati, Nimas Ririh; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This research focuses on the case of ambiguity found in Hooray textbook which is used by the sixth grade of elementary school students. The research is aimed at analyzing: 1) the types of ambiguity found in Hooray textbook, 2) the frequency of each type of ambiguity, 3) the type of ambiguity which dominantly appears, 4) describing the causes of the ambiguous sentence and 5) describing the way to disambiguate the sentences. The topic of this research is ambiguity. The objects of this research are ambiguous words, phrases and sentences which found in Hooray textbook. The type of this research is descriptive qualitative research. The data of this research are ambiguous words, phrases and sentences. The data source of this research is Hooray textbook used by the sixth grade of elementary students. The data collection technique is documentation. In data collection technique, the writer does several steps such as: 1) The writer reads the textbook that is Hooray English textbook, until the writer understands the data to be analyzed. 2) The writer identifies the ambiguous words, phrases or sentences and than gives a mark the types of ambiguity of it. 3) The writer classifies all types of ambiguity whether include in lexical ambiguity, surface structure ambiguity or deep structure ambiguity. The writer uses several theories such as from Kreidler, Kess and Fauziati to analyze the type of ambiguity. From the result of the data analysis, the research reveals that: 1) the writer finds three type of ambiguity which are lexical ambiguity, referential ambiguity and surface structure ambiguity, 2) the frequency of each type of ambiguity are 52 lexical ambiguity (29, 7%), 94 referential ambiguity (53, 7%) and 29 surface structure ambiguity (16, 6%), 3) the dominant type of ambiguity is referential ambiguity because there are 94 referential ambiguity (53, 7%), 4) the causes of ambiguity are without context, ambiguous word order, improper or missing punctuation and faulty pronoun reference and 5) the way to disambiguate the sentences which are paraphrasing, adding preposition, moving sentence construction, adding additional context and using picture.